Use of artificial intelligence deep learning in detecting peri-implant bone loss: Penggunaan artificial intelligence deep learning dalam mendeteksi terjadinya kehilangan tulang pada peri-implan - Danial, Nurul Huda; Thahir, Hasanuddin (Makassar Dental Journal, 2025)
Dental implants are now a common treatment with high survival rates and patient satisfaction. Complications of peri-implantitis are inflammation of the peri-implant tissue resulting in bone loss around the implant. Artificial Intelligence (AI), has shown re-markable success in detecting peri-implant bone loss through radiographic images. This article evaluates and analyses the use of AI deep learning in detecting peri-implant bone loss. An article search was conducted using PubMed, Scopus, Science Direct, and Cochrane published in 2019-2024. 128 articles were obtained, but 5 articles were included in the study. It was con-cluded that the application of AI deep learning has the potential to detect bone loss around dental implant tissues. Although AI models can provide good predictions, they should be seen as a support rather than a substitute in clinical decision-making.